2014
DOI: 10.1111/his.12338
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical expression of the mammalian target of rapamycin pathway in penile squamous cell carcinomas: a tissue microarray study of 112 cases

Abstract: Our results provide evidence of dysregulation of the mTOR pathway in penile carcinomas independently of HPV infection. Future clinical studies should further evaluate the prognostic and predictive usefulness of these markers in patients with penile cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 16 publications
(37 reference statements)
1
18
0
Order By: Relevance
“…The activation of the mTOR signaling pathway has recently been demonstrated in penile SCC (Chaux et al, 2014;Ferr andiz-Pulido et al, 2013a). Moreover, epidermal growth factor receptor (EGFR) is overexpressed in more than 90% of penile SCC (Lavens et al, 2010;Gou et al, 2013) and retrospective studies suggest that EGFR inhibitors may be active in this context (Carthon et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The activation of the mTOR signaling pathway has recently been demonstrated in penile SCC (Chaux et al, 2014;Ferr andiz-Pulido et al, 2013a). Moreover, epidermal growth factor receptor (EGFR) is overexpressed in more than 90% of penile SCC (Lavens et al, 2010;Gou et al, 2013) and retrospective studies suggest that EGFR inhibitors may be active in this context (Carthon et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple oncogenic signaling pathways including STAT3, PI3K/AKT, and metaloproteinases MMP2/9 contribute to PC carcinogenesis. Stankiewicz and Chaux et al showed that AKT expression positively correlated with tumor grade and prognosis of PC 39 , 40 . Yang et al identified STAT3 as one of the top oncogenic pathways upregulated in PC 41 .…”
Section: Discussionmentioning
confidence: 99%
“…In penile squamous cell carcinoma, mTOR has been shown to be overexpressed in histologically high grade cases ( 27 ). BxPC-3 cells with enriched fibroblasts may have been in a histologically high grade due to mTOR expression at the time of transplantation.…”
Section: Discussionmentioning
confidence: 99%